Probiotic Potential of Dairy Western Balkan Countries Enterococcus faecium strains - Popović, Nikola; Terzić-Vidojević, Amarela; Brdarić, Emilija; Soković Bajić, Svetlana; Djokić, Jelena; Živković, Milica; Veljović, Katarina (Archives of Pharmacy, 2023)
One of the major genera of the lactic acid bacteria family, Enterococcus sp., has a controversial status, reflected in the fact that enterococci are utilized as starter cultures and probiotics, in addition to being known to cause nosocomial infections. The qualified presumption of the safety list and the widely acknowledged safe status for Enterococcus species are absent. Rich sources of Enterococcus faecium species with possible probiotic characteristics can be found in artisanal dairy products, typically made from raw milk. To further understand the probiotic potential and health-promoting effects, this study looked at the presence of virulence factors and adhesion properties of En. faecium isolated from artisanal dairy products from Western Balkan countries.